1995
DOI: 10.1530/eje.0.1320716
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone response to growth hormone-releasing hormone (GHRH), insulin, clonidine and arginine after GHRH pretreatment in obese children: evidence of somatostatin increase?

Abstract: To clarify the possible neuroendocrine mechanisms underlying the impairment in growth hormone (GH) secretion present in obesity, the GH response to GH-releasing hormone (GHRH, N = 6), insulin hypoglycemia (N = 6), clonidine (N = 7) and arginine (N = 8) after GHRH pretreatment (1 microgram/kg iv 2 h before the tests) was evaluated in 27 obese peripubertal children and in a group of normal-weight short-normal children (N = 26). Growth hormone-releasing hormone pretreatment and all further stimuli elicited a stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…It is also theorized that obesity is associated with increased somatostatin tone. Studies have found that arginine and pyridostigmine, both somatostatin inhibitors, significantly enhance GH release in obese children who had been treated with GH-releasing hormone [6, 13]. It should be noted, however, that pyridostigmine has been found to enhance GH secretion after GHRH treatment in children with GH deficiency, familial short stature, and constitutional growth delay, as well [14].…”
Section: Discussionmentioning
confidence: 99%
“…It is also theorized that obesity is associated with increased somatostatin tone. Studies have found that arginine and pyridostigmine, both somatostatin inhibitors, significantly enhance GH release in obese children who had been treated with GH-releasing hormone [6, 13]. It should be noted, however, that pyridostigmine has been found to enhance GH secretion after GHRH treatment in children with GH deficiency, familial short stature, and constitutional growth delay, as well [14].…”
Section: Discussionmentioning
confidence: 99%
“…Indirect studies in humans using somatostatin infusion seem to support this notion as the relative GH/IGF-I response during somatostatin infusion and following withdrawal was comparable [12]. In obese and normal-weight children in whom the GH response to various stimuli was assessed after growth hormone-releasing hormone (GHRH) pretreatment, obese children exhibited similarly high GH levels as the normal weight control group only after stimulation with arginine, which is believed to act via somatostatin inhibition [13]. The alternative explanation of a GHRH hypofunction in obesity has not, however, been experimentally substantiated.…”
Section: Obesity and Regulators Of Gh Secretionmentioning
confidence: 99%
“…ARG-induced GH release has been welldocumented in human and is thought to be mediated by a decrease in somatostatin release (Locatelli et al, 1986;Alba-Roth et al, 1988;Ghigo et al, 1990a;Volta et al, 1995). In that respect, ARG has been shown to override inhibitory effects on GH secretion that are known to be mediated by an increase in somatostatin release, including glucose administration (Ghigo et al, 1992), obesity Martina et al, 1995), glucocorticoids (Giustina et al, 1992), advanced age (Ghigo et al, 1990b) and GH negative feedback (Massara et al, 1986;Torsello et al, 1988;Kelijman and Frohman, 1991;Ghigo et al, 1991).…”
mentioning
confidence: 99%